Aerobic one-step oxidation of benzene to phenol on copper exchanged HZSM5 zeolites: A mechanistic study - Tabler, Andreas; Häusser, Anette; Roduner, Emil (Journal of molecular catalysis. A, Chemical, 2013)
•Dioxygen is activated at the copper centers in the zeolite.•Cu+ oxidation by O2 and Cu2+ reduction by benzene represent a catalytic redox cycle.•Both, Brønsted acid sites and Cu ions are essential, proving bifunctional phenol formation catalysis.•The superoxide ion is the likely intermediate in a radical ionic reaction mechanism. Various Cu/HZSM5-zeolites were prepared and their catalytic properties were investigated by product analysis via GC/MS chromatography in order to trace down the mechanism of the gas phase one-step oxidation of benzene to phenol with molecular oxygen. Comparison of Cu free and Cu containing zeolites showed that the activation of O2 takes place at copper centers of the zeolite and high copper loadings lead to high yields of deep oxidation products (CO, CO2). No phenol was formed in the absence of Brønsted acid sites, i.e. on Cu/KZSM5, revealing the bifunctionality of the Cu/HZSM5 zeolite. The yields of the various oxidation products and thus the selectivity toward phenol can be influenced by variation of the relative O2 concentration in the reaction mixture, indicating the possibility of a stoichiometric use of O2. The role of the superoxide radical ion O2− as a reactive intermediate is discussed and a radical ionic reaction mechanism is suggested.